PRODUKSI LIPID ISOLAT BARU MIKROALGA LAUT Skeletonema sp. HASIL KULTUR MASSAL DI OUTDOOR SEBAGAI BAHAN BAKU BIODIESEL - Fitrah, Fitrah; Indrayani, Indrayani; Emiyarti, Emiyarti (JSIPi (Jurnal Sains dan Inovasi Perikanan) (Journal of Fishery Science and Innovation), 2022)
Skeletonema sp. is a type of marine microalgae widely studied for its  potentials a raw material for biodiesel due to fast growth, high lipid content and resistant to environmental changes. The aim of this study was to determine specific growth rate, biomass production, lipid content and lipid produksivity of a newly isolated marine microalga Skeletonema sp. mass cultivated in 1 m 2 outdoor raceway pond. This study was conducted from June - December 2019 in the hatchery of Unit PelaksanaTeknis Daerah (UPTD) Purirono Kendari. The alga species was cultivated in a 1m2 raceway pond in outdoors for  a month. The alga was cultured using f/2 medium under semi-continuous mode with harvesting every 4 days. Sampling for cell counting was done every two days whereas sampling for biomass and lipid was conducted prior to harvesting (every 4 days). The results showed that the Skeletonema sp. can grow well in a 1 m 2 outdoor raceway pond with an average specific growth rate of 0.30 d-1, biomass yield of 0.62 g/L, biomass productivity of 0.222 g/L, lipid yield of0.28 g/L from biomass dry weight, lipid content of 44.81%, and  lipid productivity of 0.092 g/L/h. This study showed that the Skeletonema sp. has the potential to be developed as a raw material for biodiesel due to its high growth rate, biomass and lipid productivity when mass cultured in outdoors.